THE RIGHT TO CONSULTATION AND FREE, PRIOR AND INFORMED CONSENT IN LATIN AMERICA: THE GOVERNMENTALITY OF THE EXTRACTION OF NATURAL RESOURCES - Bustamante, Gonzalo (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2015)
Over the last few decades, indigenous peoples in Latin America have adopted a human rights approach which demands the ratification of the International Labour Organization Convention 169 (C169), a convention that has been successfully ratified by most of Latin American countries. Most of the literature on the governance of natural resource extraction has focused on different governmental administrations and ecological policies. However, there is still a need to analyse the role of the right to consultation and ‘free, prior and informed consent’ (FPIC) within this governance structure. Using the theoretical framework of governmentality, this article aims to analyze the continuities and ruptures, as well as the tensions and advances of this form of governance by focusing on the rationalities, practices and technologies of government and power relations at play in the ratification of C169 and the implementation of FPIC in several Latin America countries. The main conclusion is that, while indigenous peoples are gaining more participation in and influence on the governance of extractive projects, national governments have colonized the right to FPIC, rendering it subordinate to their neoliberal and post-neoliberal projects. This has occurred through a rationality based on development and national interest, the use of biopolitics, ontopolitics and disciplinary power, as well as institutional and legal reforms as technologies of government – all of this having yielded little substantive implementation in comparison to a more established normative implementation. Consequently, the governmentality of most of these Latin-American countries corresponds to authoritarian governmentality.